2023
DOI: 10.1021/acsabm.2c00955
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Free Method to Control and Enhance Extracellular Vesicle Cargo Loading and Delivery

Abstract: Extracellular vesicles (EVs)�including exosomes and micro-vesicles�are involved in cell−cell communication. EVs encapsulate different types of molecules such as proteins or nucleotides and are long-lasting contenders for the establishment of personalized drug delivery systems. Recent studies suggest that the intrinsic capacities for uptake and cargo delivery of basic EVs might be too limited to serve as a potent delivery system. Here, we develop two synergistic methods to, respectively, control EV cargo loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…After the donor cells are loaded with target molecules, the MVBs can deliver active molecules to extracellular vesicles via ILVs, as shown in Figure 2 . 19 , 20 Notably, the co-incubation method is one of the most widely used drug loading strategies, and they put the drugs and donor cells together, which induces new biological characteristics in exosomes by altering culture conditions and the incubation environment of donor cells. Critically, this method involves selecting suitable donor cells, such as fibroblasts and hematopoietic stem cells, and then incubating them with drugs suspended in the culture medium.…”
Section: Drug Loading Into Exosomes: Methods and Strategiesmentioning
confidence: 99%
“…After the donor cells are loaded with target molecules, the MVBs can deliver active molecules to extracellular vesicles via ILVs, as shown in Figure 2 . 19 , 20 Notably, the co-incubation method is one of the most widely used drug loading strategies, and they put the drugs and donor cells together, which induces new biological characteristics in exosomes by altering culture conditions and the incubation environment of donor cells. Critically, this method involves selecting suitable donor cells, such as fibroblasts and hematopoietic stem cells, and then incubating them with drugs suspended in the culture medium.…”
Section: Drug Loading Into Exosomes: Methods and Strategiesmentioning
confidence: 99%
“…For instance, Es-Haghi et al 134 developed a fusion protein of EVs membrane protein CD9 and RNA-binding protein AGO2 (hCD9.hAGO2) to achieve the RNA loading, and the results indicated that EVs contained high levels of miRNA and these engineered EVs could also transfer RNA cargo to recipient cells more efficiently. Bui et al 135 achieved endogenous cargo loading by interacting with CD63 and improved the delivery efficiency of EVs by fusion without requiring any viral fusogenic protein. The results indicated that the delivery efficiency of the cargo was significantly improved by the overexpressing of Syncytin-1.…”
Section: The Engineering Strategy Of Evsmentioning
confidence: 99%
“…A VGV-G-free method of rapamycin-FKBP-FRB EV cargo loading has been developed through the use of Syncytin-1, an endogenous human fusogen protein. 117 …”
Section: Engineered Ev Cargo Loading Strategiesmentioning
confidence: 99%